THE NATURE AND IMPLICATIONS OF CONTEXTUAL INFLUENCES ON TRANSFORMATIONAL LEADERSHIP: A CONCEPTUAL EXAMINATION - Pawar, Badrinarayan Shankar; Eastman, Kenneth K. (Academy of Management Review, 1997)
Badrinarayan Shankar Pawar, Kenneth K. Eastman, The Nature and Implications of Contextual Influences on Transformational Leadership: A Conceptual Examination, The Academy of Management Review, Vol. 22, No. 1 (Jan., 1997), pp. 80-109